2019
DOI: 10.3390/app9235003
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin and Cybersecurity: Temporal Dissection of Blockchain Data to Unveil Changes in Entity Behavioral Patterns

Abstract: The Bitcoin network not only is vulnerable to cyber-attacks but currently represents the most frequently used cryptocurrency for concealing illicit activities. Typically, Bitcoin activity is monitored by decreasing anonymity of its entities using machine learning-based techniques, which consider the whole blockchain. This entails two issues: first, it increases the complexity of the analysis requiring higher efforts and, second, it may hide network micro-dynamics important for detecting short-term changes in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We posited the assumption that miners should receive a mining reward (input address) from the mining pool and keep it in their wallet (miner address) before spending it (output address) on services (e. g. exchange, mixer, or marketplace). We used a known entity dataset from WalletExplorer.com with entity type classification from Zola et al [27]. We report the percentage of addresses and Bitcoin values for each entity type in Table II.…”
Section: B Miners Addresses Association With Known Entitiesmentioning
confidence: 99%
“…We posited the assumption that miners should receive a mining reward (input address) from the mining pool and keep it in their wallet (miner address) before spending it (output address) on services (e. g. exchange, mixer, or marketplace). We used a known entity dataset from WalletExplorer.com with entity type classification from Zola et al [27]. We report the percentage of addresses and Bitcoin values for each entity type in Table II.…”
Section: B Miners Addresses Association With Known Entitiesmentioning
confidence: 99%
“…Baumann et al [41] found that over time, the degree distribution of Bitcoin converges to become a scale-free network. F. Zola et al [42] developed a method for entity classification in Bitcoin. They compared the similarities of physical transaction patterns over time and studied whether they repeated certain transaction patterns in different batches of Bitcoin transaction data.…”
Section: Related Workmentioning
confidence: 99%
“…This platform represents a database where information about known entities and their related addresses are stored. This database is continuously updated and has been used as a "ground truth" for many Bitcoin-related studies, such as [2], [33], [24]. Here, Wallet-Explorer data were divided into six classes:…”
Section: A Blockchain Datamentioning
confidence: 99%
“…This calls for novel approaches that can augment the dataset of such critical services with synthetically created instances, ultimately aiming to improve classification results. The most common technique currently adopted to address the imbalance problem is to not consider certain classes [33], or to apply various types of sampling methods, like over-sampling for the least represented classes [11] or undersampling for the most represented ones [18].…”
Section: Introductionmentioning
confidence: 99%